Reputation management : the key to successful public relations and corporate communication - Doorley, John.; Garcia, Helio Fred (New York : Routledge, 2015)
'Reputation Management is a how-to guide for students and professionals, as well as CEOs and other business leaders. It rests on the premise that reputation can be measured, monitored, and managed. Organized by corporate communication units including media relations, employee communication, government relations, and investor relations, the book provides a field-tested guide to corporate reputation problems such as leaded memos, unfair treatment by the press, and negative rumors, and focuses on practical solutions. Each chapter is fleshed out with the real-world experience of the authors and contributors, who come from a wide range of professional corporate communication backgrounds'--
'Reputation Management is a how-to guide for students and professionals, as well as CEOs and other business leaders. It rests on the premise that reputation can be measured, monitored, and managed. Organized by corporate communication units including media relations, employee communication, government relations, and investor relations, the book provides a field-tested guide to corporate reputation problems such as leaked memos, unfair treatment by the press, and negative rumors, and focuses on practical solutions. Each chapter is fleshed out with the real-world experience of the authors and contributors, who come from a wide range of professional corporate communication backgrounds'--
Keywords: Public relations; Communication in organizations; LANGUAGE ARTS & DISCIPLINES / Communication Studies; BUSINESS & ECONOMICS / Industries / Media & Communications Industries; SOCIAL SCIENCE / Media Studies